The Significance of Autoantibody Changes Over Time in Primary Biliary Cirrhosis. Issue 4 (1st October 2015) - Tana, Michele M.; Shums, Zakera; Milo, Jay; Norman, Gary L.; Leung, Patrick S.; Gershwin, M. Eric; Noureddin, Mazen; Kleiner, David E.; Zhao, Xiongce; Heller, Theo; Hoofnagle, Jay H.
Abstract: Objectives: In primary biliary cirrhosis (PBC), the antimitochondrial antibody is a cornerstone of diagnosis, but there have been conflicting reports about the correlation of autoantibodies with disease stage and prognosis. We studied whether autoantibody levels changed over time and sought correlations with clinical outcomes in a cohort of patients with PBC. Methods: We tested serial serum samples from patients with PBC at a research institution for several autoantibodies. Long-term clinical follow-up data were used to calculate the slopes (change over time) for autoantibodies, platelet count, Ishak fibrosis score, biopsy copper, and number of portal areas with bile ducts. An adverse clinical outcome was defined as hepatic decompensation, development of hepatocellular carcinoma, liver transplantation, or liver-related death. We performed linear or logistic regression or Fisher exact test as appropriate, adjusting for multiple comparisons. Results: Twenty-seven patients with PBC with 145 serum samples were studied. Of the cohort, 85% was white, 81% was female, and median follow-up time was 20 years. Of the autoantibodies tested, only sp100 changed significantly over time. The sp100 slope was inversely associated with the Ishak fibrosis slope (parameter estimate, −0.05; P = .0003). Conclusions: While changes in most autoantibodies over time do not seem to correlate with clinical outcomes in PBC, a change in the sp100 autoantibody level may have prognostic utility with respect to the development of fibrosis on liver biopsy.